Intercellular transfer of miR-126-3p by endothelial microparticles reduces vascular smooth muscle cell proliferation and limits neointima formation by inhibiting LRP6. (March 2017) - Jansen, Felix; Stumpf, Tobias; Proebsting, Sebastian; Franklin, Bernardo S.; Wenzel, Daniela; Pfeifer, Philipp; Flender, Anna; Schmitz, Theresa; Yang, Xiaoyan; Fleischmann, Bernd K.; Nickenig, Georg; Werner, Nikos
Abstract: Background: Vascular smooth muscle cell (VSMC) proliferation is of importance in the pathogenesis of vascular diseases such as restenosis or atherosclerosis. Endothelial microparticles (EMPs) regulate function and phenotype of target endothelial cells (ECs), but their influence on VSMC biology is unknown. We aim to investigate the role of EMPs in the regulation of vascular smooth muscle cell (VSMC) proliferation and vascular remodeling. Methods and results: Systemic treatment of mice with EMPs after vascular injury reduced neointima formation in vivo. In vitro, EMP uptake in VSMCs diminished VSMC proliferation and migration, both pivotal steps in neointima formation. To explore the underlying mechanisms, Taqman microRNA-array was performed and miR-126-3p was identified as the predominantly expressed miR in EMPs. Confocal microscopy revealed an EMP-mediated miR-126 transfer into recipient VSMCs. Expression of miR-126 target protein LRP6, regulating VSMC proliferation, was reduced in VSMCs after EMP treatment. Importantly, genetic regulation of miR-126 in EMPs showed a miR-126-dependent inhibition of LRP6 expression, VSMC proliferation and neointima formation in vitro and in vivo, suggesting a crucial role of miR-126 in EMP-mediated neointima formation reduction. Finally, analysis of miR-126 expression in circulating MPs in 176 patients with coronary artery disease revealed a reduced PCI rate in patients with high miR-126 expression level, supporting a central role for MP-incorporated miR-126 in vascular remodelling. Conclusion: EMPs reduce VSMC proliferation, migration and subsequent neointima formation by delivering functional miR-126 into recipient VSMCs. Highlights: Endothelial microparticles (EMPs) transfer functional microRNA-126 into target VSMCs Transfer of microRNA-126 via EMPs into target vessels reduces vascular remodelling Genetic regulation of microRNA-126 within EMP determines their effect in target cells